Hybrid photocatalysts of ZnO obtained by waste valorization combined with reduced graphene oxide. (2020) - Molina, J.; Añó, E.; Simorte, J.; Valero-Gómez, A.; Bosch, F.
Abstract: Valorized ZnO has been combined with reduced graphene oxide (RGO) to produce hybrid photocatalysts with enhanced photocatalytic activity. Electrostatic self-assembly between negatively charged graphene oxide (GO) and positively charged ZnO nanoparticles has been used to produce hybrid photocatalysts with different concentration of GO (0.1 %, 0.5 %, 1 %, 2 %, 5 %). Thermal treatment of ZnO/GO has been used to achieve the reduction of GO to RGO. The performance of the photocatalysts has been tested in the degradation of methylene blue solutions, where an increase of the photocatalytic activity was observed with the increase of RGO in the photocatalysts